THE GREAT SILK ROAD CULTURAL LIFE (ResearchJet Journal of Analysis and Inventions, 2021)
The Great Silk Road is a unique event in the history of human development, its desire to unite and share cultural values, to reach markets for the sale of living space and products. According to an Eastern saying, "Sitting is a mat, walking is a river." Moving is life, traveling, globalization has always been the driving force of development. This intercontinental trade route, the largest in human history, connected Europe and Asia, from the ancient Roman Empire to the ancient Japanese capital of Nara. Of course, trade between East and West dates back to ancient times, but these were separate parts of the Great Way that was to be built. The development of trade relations was largely facilitated by the discovery and mining of semi-precious stones in the mountains of Central Asia - lazurite, nephrite, onyx, turquoise, which are highly valued in the East. For example, there was a "lazurite route" from Central Asia to Iran, Mesopotamia, and even Egypt, where lazurite was transported. At the same time, the "jade road" was built, which connected the districts of Hotan and Yorkent with the regions of northern China. In addition, agate was imported from Sogdiana and Bactria to Central Asia, and turquoise was imported from Khorezm. All of these routes eventually merged into the Great Silk Road. Historians believe that the real beginning of the great road connecting the caravan routes from Central Asia to the West and South and from China to East Turkestan dates back to the middle of the second century BC, when the first Western lands for the Chinese were the Central Asian states.